Dampak Father Involvement dalam Pengasuhan Remaja - Diva Ingriani; Ulfa Dwina; Muhammad Fajar Yuwanda; Kania Jeanrita; Nurul Sabrina (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
This study aims to explore the impact of father involvement in adolescent parenting and how this role affects children's emotional, social, and academic development. Adolescence is a critical period marked by significant changes in physical, cognitive, and emotional aspects. Active father involvement in children's lives has been shown to contribute positively to adolescent achievement motivation and emotional well-being. Through a qualitative approach and literature analysis, this study identified various forms of support provided by fathers, including affectionate support, parenting, and involvement in daily activities. The results showed that the higher the level of father involvement, the better the development of adolescents in facing life challenges. These findings emphasize the importance of the role of fathers in shaping children's character and life values, and provide recommendations to increase awareness of the importance of father involvement in parenting.